Financial and social outcomes, Employment Strategy, FNE, Evaluation and Public Policy, Territorial Northeast - Carlos AraÃjo Cruz Filho (2013)
This work has the objective to evaluate the Nordeste Territorial Strategy of the Banco do Nordeste, a developed bank from Northeast Region from Brazil; a strategy organized and worked in TejuÃuoca City, in the CearÃ State, at the period of 2008 to 2012, when a lot of institutional actions from Banco do Nordeste and partners had been implemented in the locality, also and mainly on account of the disposal of financial resources through the Region Public Fund, known as Fundo Constitucional do Nordeste (FNE), intended to enterprises that attend the requirements of the program in that Region. The FNE is part of a roll of public politics of the Federal Government with the responsibility to support companies and entrepreneurs of any size who exert productive activities in the Northeast Region, North of Minas Gerais and North of Espirito Santo. This work evaluates if the objectives considered for the strategy implemented through Banco do Nordeste has being correctly attended, since this program deals mainly with public resources. Also, this work verifies and indicates if changes or improvements in the conditions of life in terms of job and income creation had been reached by the beneficiaries of the loan resources granted by the Bank. Researches were made through questionnaires to the managers of the program, customers that had been attended through, Agents of Development and others stakeholders, objectifying to catch additional information. Finally, the proposal of this work aims also to deal with political, instrumental and technical questionings, considering the possibility of creation of new ranks of job and, consequently, improvement of life conditions of all the involved ones.